Redesain Tempat Penyimpanan Sementara Limbah B3 di Workshop PT. Purna Baja Harsco - Risza Wisdayana; Frebhika Sri Puji Pangesti; Ade Ariesmayana (Fakultas Teknik, 2022)
B3 waste generated by PT. Purna Baja Harsco in one day in the form of used Majun 19.19 liters, used batteries 1.11 liters and used oil 6.02 liters. The purpose of this study was to determine the types and characteristics of B3 waste generated from maintenance and repair activities at the PT Purna Baja Harsco workshop, to identify and evaluate B3 waste management at the PT Purna Baja Harsco workshop, and to redesign the B3 waste TPS in accordance with applicable regulations. The research method for the design of the B3 waste TPS design begins with collecting data on the types and characteristics of B3 waste, the weight and volume of B3 waste, packaging planning, and calculating the area of the Planning TPS. The results showed that on average in one day it can produce 19.19 liters of used waste, 1.11 liters of used batteries and 6.02 liters of used oil. In storage, there are still several things that are not in accordance with applicable regulations, for the latest B3 waste TPS considering aspects of capacity, location, and facilities in the form of reservoirs, ventilation, lighting, roof construction, extinguishers and means of transportation. The 3 waste TPS is planned to be able to store 2,047 liters of used cotton with a shelf life of 90 days, 511 liters (24 units) of used batteries with a shelf life of 180 days and 2,880 liters of used oil with a shelf life of 365 days.